Define learning outcomes in terms of processes and contents: the cognitive operations - Roberto Trinchero (Firenze University Press, 2022)
How is it possible to define learning outcomes in school education? How can they be useful for rationalizing programming, teaching, learning and evaluation? The article describes the potential associated with a good definition of learning outcomes in terms of thought processes and learning contents, which define the cognitive operations that the learner must be able to implement in the facing of specific tasks. A model for defining learning outcomes that uses descriptors with explicit and shared formulation (R-I-Z-A model) is then presented. The model can be used both to operationalize skills and competences of the student.   Definire i learning outcomes in termini di processi e contenuti: le operazioni cognitive. Come è possibile definire i learning outcomes nella formazione scolastica? Come possono essere utili per razionalizzare la programmazione, la didattica, gli apprendimenti e la valutazione? L'articolo descrive le potenzialità legate a una buona formulazione dei learning outcomes in termini di processi di pensiero e contenuti di apprendimento, i quali definiscono le operazioni cognitive che l'allievo deve essere in grado di mettere in atto di fronte a consegne specifiche. Viene poi presentato un modello di definizione di learning outcomes che utilizza descrittori dotati di formulazione esplicita e condivisa (modello R-I-Z-A), che può essere utilizzato sia per operazionalizzare competenze, sia per operazionalizzare singole conoscenze/abilità dello studente.